Individualization of Teaching in the U.S.A. - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 1993)
The quest has started at the end of the 19th century and the beginning of the 20th century for more effective teaching methods and forms of organization that would take into account children’s individual characteristics: the pace of activities, interests, preferences, needs, abilities, motivation, etc. Especially clear shifts towards individual teaching are observed in pedagogy and school practice in the United States. Already the early progressivists (F. Parker, P. Search) not only criticized the mass, standardized teaching, but also explored the principle of individual approach, sought the methods not only to know the individuality, but also to activate it in the teaching process. The experience and ideas of the early progressivists have been theoretically summed by J. Dewey, who have developed a new pedagogical theory based on pragmatic philosophy and psychology, which became the foundation of other educational systems developing ideas of individualization, differentiation, activation of teaching. These systems are used for various forms of individualization: abandoning classes in favour of homogeneous groups for some time and only some of the things; individualized teaching under the rate of activities (the Dalton plan), according to the teaching materials (Winnetka plan); individualized teaching tasks within heterogeneous classes, etc.